2017
DOI: 10.3847/1538-4357/835/2/147
|View full text |Cite
|
Sign up to set email alerts
|

Theory and Transport of Nearly Incompressible Magnetohydrodynamic Turbulence

Abstract: The theory of nearly incompressible magnetohydrodynamics (NI MHD) was developed largely in the early 1990s, together with an important extension to inhomogeneous flows in 2010. Much of the focus in the earlier work was to understand the apparent incompressibility of the solar wind and other plasma environments, and the relationship of density fluctuations to apparently incompressible manifestations of turbulence in the solar wind and interstellar medium. Further important predictions about the “dimensionality”… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
352
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 275 publications
(378 citation statements)
references
References 100 publications
25
352
1
Order By: Relevance
“…As a final remark, we note that the good agreement between the 2D and the 3D numerical results may find theoretical support and a possible interpretation in Zank et al (2017). There, the nearly incompressible magnetohydrodynamic turbulence in the intermediate-and small-beta regimes is shown to comprise the presence of majority 2D and minority slab fluctuations.…”
Section: Discussionmentioning
confidence: 90%
“…As a final remark, we note that the good agreement between the 2D and the 3D numerical results may find theoretical support and a possible interpretation in Zank et al (2017). There, the nearly incompressible magnetohydrodynamic turbulence in the intermediate-and small-beta regimes is shown to comprise the presence of majority 2D and minority slab fluctuations.…”
Section: Discussionmentioning
confidence: 90%
“…Our results (in the present paper for fast solar wind and in Perrone et al (2016) for slow solar wind) show that the vortex-like structures are the dominant form in the observed structures; thus, they may play a major role in the dynamics of the solar wind plasma at ion scales. A very recent theoretical study in nearly incompressible magnetohydrodynamic (NI MHD) turbulence by Zank et al (2017) has shown that two-dimensional vortex structures are explicitly predicted by the model. In particular the NI MHD formulation describes the transport of majority 2D, and minority slab, turbulence throughout the solar wind.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The development of magnetic turbulence transport models (TTMs, see, e.g., Zank et al 1996Zank et al , 2012Zank et al , 2017Breech et al 2008;Pei et al 2010a;Oughton et al 2011;Engelbrecht & Burger 2013a;Guo & Florinski 2016), which allows us to have a better scenario of the heliosphere, plays an important role in the ab initio models for cosmic ray diffusion. Especially in the numerical modulation study, the analytical expressions of diffusion is essential, which are directly based on the spatial dependence of magnetic turbulence.…”
Section: Magnetic Turbulence Throughout the Inner-heliospherementioning
confidence: 99%